Wear Behavior and Surface Quality of Dental Bioactive Ions-Releasing Resins Under Simulated Chewing Conditions - Garcia, Isadora Martini; Balhaddad, Abdulrahman A.; Aljuboori, Noorhan; Ibrahim, Maria Salem; Mokeem, Lamia; Ogubunka, Akudo; Collares, Fabrício Mezzomo; Melo, Mary Anne Sampaio de (Frontiers in Oral Health, 2021)
Bioactive materials can reduce caries lesions on the marginal sealed teeth by providing the release of ions, such as calcium, phosphate, fluoride, zinc, magnesium, and strontium. The presence of such ions affects the dissolution balance of hydroxyapatite, nucleation, and epitaxial growth of its crystals. Previous studies mostly focused on the ion-releasing behavior of bioactive materials. Little is known about their wear behavior sealed tooth under mastication. This study aimed to evaluate the wear behavior and surface quality of dental bioactive resins under a simulated chewing model and compare them with a resin without bioactive agents. Three bioactive resins (Activa, BioCoat, and Beautifil Flow-Plus) were investigated. A resin composite without bioactive agents was used as a control group. Each resin was applied to the occlusal surface of extracted molars and subjected to in vitro chewing simulation model. We have assessed the average surface roughness (Ra), maximum high of the profile (Rt), and maximum valley depth (Rv) before and after the chewing simulation model. Vickers hardness and scanning electron microscopy (SEM) also analyzed the final material surface quality). Overall, all groups had increased surface roughness after chewing simulation. SEM analysis revealed a similar pattern among the materials. However, the resin with polymeric microcapsules doped with bioactive agents (BioCoat) showed increased surface roughness parameters. The material with Surface Pre-reacted Glass Ionomer (Beautifil Flow-Plus) showed no differences compared to the control group and improved microhardness. The addition of bioactive agents may influence surface properties, impairing resin composites' functional and biological properties. Future studies are encouraged to analyze bioactive resin composites under high chemical and biological challenges in vitro with pH cycles or in situ models.